2013
DOI: 10.1371/journal.pone.0075508
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of White Matter Integrity Related to the Season of Birth in Schizophrenia: A DTI Study

Abstract: In schizophrenia there is a consistent epidemiological finding of a birth excess in winter and spring. Season of birth is thought to act as a proxy indicator for harmful environmental factors during foetal maturation. There is evidence that prenatal exposure to harmful environmental factors may trigger pathologic processes in the neurodevelopment, which subsequently increase the risk of schizophrenia. Since brain white matter alterations have repeatedly been found in schizophrenia, the objective of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 68 publications
(72 reference statements)
2
14
1
Order By: Relevance
“…In both neuropathology and neuroimaging, it is uncertain whether white matter changes are an intrinsic component of schizophrenia or are the consequence of neuroleptic treatment, social deprivation, or other epiphenomena related to suffering from a chronic psychiatric disorder. A number of studies have suggested that the DTI abnormalities in schizophrenia are confounded by multiple factors, including the duration of illness and treatment with antipsychotic medications (Konopaske et al, 2006(Konopaske et al, , 2008, age (Kochunov et al, 2013a(Kochunov et al, , 2013bGiezendanner et al, 2013;Mandl et al, 2013), sex of the subjects (Savadjiev et al, 2014), and even heavy cigarette smoking (Cullen et al, 2012;Kochunov et al, 2013aKochunov et al, , 2013b.…”
Section: Pathological Changes Of White Matter In Schizophreniamentioning
confidence: 99%
“…In both neuropathology and neuroimaging, it is uncertain whether white matter changes are an intrinsic component of schizophrenia or are the consequence of neuroleptic treatment, social deprivation, or other epiphenomena related to suffering from a chronic psychiatric disorder. A number of studies have suggested that the DTI abnormalities in schizophrenia are confounded by multiple factors, including the duration of illness and treatment with antipsychotic medications (Konopaske et al, 2006(Konopaske et al, , 2008, age (Kochunov et al, 2013a(Kochunov et al, , 2013bGiezendanner et al, 2013;Mandl et al, 2013), sex of the subjects (Savadjiev et al, 2014), and even heavy cigarette smoking (Cullen et al, 2012;Kochunov et al, 2013aKochunov et al, , 2013b.…”
Section: Pathological Changes Of White Matter In Schizophreniamentioning
confidence: 99%
“…Several recent publications suggest that changes observed within white matter in schizophrenia might also be confounded by other factors, including age, life style, environmental factors, and so on. For example, Giezendanner et al [28] observed a relationship between season of birth and fractional anisotropy changes in schizophrenia (lower fractional anisotropy in those born in winter). For example, Kochunov et al [27 & ] reported accelerated fractional anisotropy decline with age in schizophrenia, but not in major depression.…”
Section: Important Considerations In White Matter Schizophrenia Researchmentioning
confidence: 99%
“…Evidence obtained from animal models and epidemiological studies suggests that this disease involves an aberrant brain cortex and hippocampal formation caused by external insults, including maternal infections, vitamin deficiencies, or psychological stress . Importantly, alterations in the photoperiod during pregnancy have been correlated with the development of SZ when the child reaches adulthood …”
Section: Introductionmentioning
confidence: 99%